2016
DOI: 10.1007/s40744-016-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Treatment and Management of Pediatric Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disorder in which 20 % of patients are diagnosed in childhood. Childhood-onset SLE is associated with higher morbidity and mortality than adult-onset SLE. The aims of disease management with early immunosuppression are to decrease disease activity and improve quality of life. A multidisciplinary approach is necessary due to the complexity of lupus in pediatric patients. It is important to provide patients with high quality of care and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 41 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Groups were further divided into two according to the number of cSLE patients followed by LAPR in the last year: group A (≥ 25 patients in the last year) and group B (< 25 patients). A higher frequency of full-time job (55 vs. 21%, p < 0.0001) and work in a public university hospital (65 vs. 40%, p = 0.001) was observed in group A compared to group Clinical trial participation cSLE patients participated in clinical trial 40 (25) Issues observed in cSLE adolescents (at least one patient) Non-adherence of medications 156 (97) B. A significantly lower frequency of only private health insurance was observed in group A compared to group B (12 vs. 28%, p = 0.0100).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Groups were further divided into two according to the number of cSLE patients followed by LAPR in the last year: group A (≥ 25 patients in the last year) and group B (< 25 patients). A higher frequency of full-time job (55 vs. 21%, p < 0.0001) and work in a public university hospital (65 vs. 40%, p = 0.001) was observed in group A compared to group Clinical trial participation cSLE patients participated in clinical trial 40 (25) Issues observed in cSLE adolescents (at least one patient) Non-adherence of medications 156 (97) B. A significantly lower frequency of only private health insurance was observed in group A compared to group B (12 vs. 28%, p = 0.0100).…”
Section: Resultsmentioning
confidence: 94%
“…Conversely, we identified limited access for specialized multidisciplinary approach required for satisfactory care, such as psychological support, dental care, palliative care support, and speech and language therapy. Indeed, the relevance of the availability of these resources for better management of cSLE was previously emphasized [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Class VI (advanced-stage lupus nephritis) designates those biopsies with ≥90% global glomerulosclerosis and in which there is clinical or pathologic evidence that the sclerosis is attributable to lupus nephritis. [1,8,9]…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In adults, hydroxychloroquine can be used as an alternative agent to treat antihistamine-refractory chronic spontaneous urticaria (CSU). 3 It is unknown whether hydroxychloroquine is safe and effective for treating antihistamine-refractory CSU in children.…”
mentioning
confidence: 99%
“…2 Hydroxychloroquine has been used safely at up to 10 mg/kg per day to treat childhood autoimmune and inflammatory conditions, including systemic lupus erythematosus and surfactant protein C deficiency. 1,7 Hydroxychloroquine is generally well tolerated, with gastrointestinal symptoms and macular rash the most common adverse effects. Ocular problems, including corneal deposits and irreversible retinopathy, are potentially serious side effects, although the risk of retinal damage is <1% when hydroxychloroquine is used at low doses (≤5 mg/kg per day) for a duration of <5 years.…”
mentioning
confidence: 99%